Interrelationships between BMI, skinfold thicknesses, percent body fat, and cardiovascular disease risk factors among U.S. children and adolescents. Issue 1 (December 2015) - Freedman, David; Ogden, Cynthia; Kit, Brian
Abstract Background Although the estimation of body fatness by Slaughter skinfold thickness equations (PBFSlaughter ) has been widely used, the accuracy of this method is uncertain. We have previously examined the interrelationships among the body mass index (BMI), PBFSlaughter, percent body fat from dual energy X-ray absorptiometry (PBFDXA ) and CVD risk factor levels among children who were examined in the Bogalusa Heart Study and in the Pediatric Rosetta Body Composition Project. The current analyses examine these associations among 7599 8- to 19-year-olds who participated in the (U.S.) National Health and Nutrition Examination Survey from 1999 to 2004. Methods We analyzed (1) the agreement between (1) estimates of percent body fat calculated from the Slaughter skinfold thickness equations and from DXA, and (2) the relation of lipid, lipoprotein, and blood pressure levels to BMI, PBFSlaughter and PBFDXA . Results PBFSlaughter was highly correlated (r 0.85) with PBFDXA . However, among children with a relatively low skinfold thicknesses sum (triceps + subscapular), PBFSlaughter underestimated PBFDXA by 8 to 9 percentage points. In contrast, PBFSlaughter overestimated PBFDXA by 10 points among boys with a skinfold thickness sum ≥ 50 mm. After adjustment for sex and age, lipid levels were related similarly to the body mass index, PBFDXA and PBFSlaughter . There were, however, small differences in associations with blood pressure levels: systolic blood pressure was more strongly associated with body mass index, but diastolic blood pressure was more strongly associated with percent body fat. Conclusions The Slaughter equations yield biased estimates of body fatness. In general, lipid and blood pressure levels are related similarly to levels of BMI (following adjustment for sex and age), PBFSlaughter, and PBFDXA .